Development of a solar photovoltaic backpack sprayer - Sasaki, Robson Shigueaki; Teixeira, Mauri Martins; Filho, Delly Oliveira; Cesconetti, Carlos Júnio; Silva, Anderson Candido; Leite, Daniel Mariano (Federal University of Piauí, 2014)
Backpack solar photovoltaic sprayers have appeared in the market with the aim of improving spraying quality and reducing physical effort for the operator. Queries related to the duration and how to charge batteries are very common and in general they become a barrier for using this equipment in the field. With the objective to better such sprayers, this work has aimed to develop and evaluate a solar photovoltaic backpack sprayer. An electric backpack sprayer MTS brand, model Spritz 18, was used. An aluminum structure was designed and built for fixing two photovoltaic cells, Kyocera brand, model KS5. The evaluation of equipment was made for the instantaneous power generated by the photovoltaic panel with the operator in movement and with the sprayer in static, as well as the potential use of the system. At the end it was verified that the average of the instantaneous power generated was of 1.4 and 2.18 W, for in movement and in static respectively. It was observed that the developed system has wide applicability. It may be applied for field use; it may also optimize the duration of the battery up to 45% and make possible the use of backpack electric sprayers in remote or distant locations, where there is no electric supply system, once it makes possible charging the batteries just using solar energy.